Supercritical carbon dioxide fractionation of pithecellobium jiringan jack seed compositions using fast gas chromatography time of flight mass spectrometry - Nik Abdul Rahman, Nik Norulaini; Sarker, Md. Zaidul Islam; C. Y., Mohd Azizi; I., Zhari; M. N., Noramin; Ferdosh, Sahena; Abd Kadir, Mohd Omar (Wiley-Blackwell, 2011)
The volatile oil components of ground Pithecellobium jiringan seeds were fractionated using supercritical carbon dioxide (SC-CO2) at 80C and 6,000 psi. The extract was collected every 20 min and the yield was successively extracted into five fractions; thus, the total extraction time was 100 min. The yields (volatile oils) were analyzed with fast gas chromatography/time of flight mass spectrometry (Fast GC-MS-TOF) and 55 components were identified. The major components were found to be fatty acids, ally sulfur, vitamin E, terpenoids, and flavonoid and alkaloid compounds. The major components were present at different percentages in each fraction, where some compounds were more dominant in fraction 1 and extracted in the first 20 min where others were more dominant in later fractions. However, the SC-CO2 and GC-MS-TOF may be regarded as new analytical tools for the separation and identification of chemical components from P. jiringan jack seeds. Substances extracted from P. jiringan jack seeds could be evaluated for anti-diabetic and anti-hypertensive effects.